Recent progress on DNA methylation in psoriasis - Lin, Zhaoping; Wu, Xiaoting; Hong, Xuqin; Luo, Dongying; Li, Hui; Ma, Fei; Huang, Cong; Yu, Bo; Gao, Jing; Shen, Changbing (Frontiers in Genetics, 2025)
Psoriasis is a chronic, recurrent, inflammatory disease that is affected by genetic, immunological, epigenetic, and environmental factors. With the development of biotechnology, research on the pathogenesis of psoriasis has deeply focused on the field of epigenetics, and great progress has been made. Epigenetics is the study of heritable changes in gene expression or cell phenotypes without altering the DNA sequence. DNA methylation (DNAm) alterations are the most common epigenetic phenomena and are widely studied. Many studies have shown that DNAm plays a key role in the pathogenesis of psoriasis, and some differentially methylated sites may be potential targets for the treatment of psoriasis. Here, we review and summarize the recent progress on DNAm in psoriasis.